How does the environmental state "see" endangered marine animals?. Issue 124 (October 2021) - Doebeli, Anna Gabriela; Magnuson, Briana; Yoon-Henderson, Kihan; Collard, Rosemary; Dempsey, Jessica; Walter, Michele (River); Carre, Marianne; Corrado, Maggy; Dhaliwal, Rajdeep; Giesting, Anna; Gonchar, Karina; Hsu, Chris; et al.
Highlights: Marine species are declining globally despite the emergence of "environmental states". Endangered marine animals (EMAs) in Canada are threatened by industrial activities. From 2002–2019, the state authorized 31 of 32 projects with potential impacts to EMAs. Environmental assessments consistently predict insignificant impacts to EMAs. The state sees EMAs in simplified and strategically illegible ways. Abstract: How does the state see nature? Has the emergence of "environmental states" with significant environmental laws and policy changed the state's vision towards nonhumans, particularly endangered wildlife? These are key questions in a paradoxical context where over the past half century, endangered wildlife have largely continued to decline amid expanding state environmental legislation. Towards answers, we analyze how endangered marine animals in Canada are considered in federal environmental assessments (EAs) that inform state decisions about whether to authorize major development projects. We conducted an inductive content analysis of all federal EAs for projects with potential adverse effects for one or more of the 14 endangered marine vertebrates in Canada. Of 32 projects, 31 were approved, 30 of which were predicted to have no or insignificant impacts on endangered marine species, despite a litany of potential impacts. This analysis reveals four main justifications for predicting insignificant impacts: unproven mitigation measures; species are presumed to have a low likelihood of occurrence in project areas; species behaviour is believed to reduce the likelihood of impacts; and project impacts are characterized as minor compared to existing activity. A consistent vision of nature underpins these justifications: the state sees marine species and ocean ecologies in a simplified manner, while these species also remain strategically illegible. Simplification and strategic illegibility both devalue endangered marine animals, suggesting EA is failing endangered marine species by facilitating the state's ability to prioritize development over species recovery.